Follicular lymphoma manifests as multiple erosive and proliferative lesions of the oral mucosa: case report and brief literature review - Yuqi Wu; You Zhang; Chunyu Li; Yulang Xie; Sixin Jiang; Yuchen Jiang; Yan Qiu; Xiaobo Luo; Qianming Chen (BMC Oral Health, 2022)
Abstract Background Erosion is one of the most common and basic lesions of oral mucosal diseases. Long-term refractory oral erosions, induced by autoimmune blistering diseases, infectious diseases, malignant diseases, and some rare conditions, may substantially reduce the quality of life of patients or even constitute a life-threatening condition, resulting in a clinical dilemma regarding the accurate diagnosis and precise management of these diseases. As a special type of malignant lymphoma, most lesions of follicular lymphoma (FL) in the oral mucosa present as masses or swelling of the oral mucosa, while emerging novel presentations lead to intractable diagnoses. Hence, diagnostic algorithms for such diseases are clinically required.  Case presentation A 55-year-old female patient presented to the clinic with long-lasting oral mucosal erosions and proliferative lesions. Blood tests, pathological examinations of oral lesions including haematoxylin–eosin (HE) staining, and direct immunofluorescence precluded all of the potential diagnoses described previously. Unexpectedly, positron emission tomography/computed tomography (PET/CT) and abdominal CT of the patient revealed a dense mass in the retroperitoneal area, and the final diagnosis of the retroperitoneal mass was FL. After three courses of chemotherapy conducted by the haematologist, the erosion and proliferative lesions in the patient's oral mucosa had significantly improved. HE and immunohistochemical staining results of intraoral lesions also confirmed it as oral FL. The successful diagnosis of FL in this case is of great clinical significance, as the oral and abdominal FL were treated in a timely manner to avoid unfavourable outcomes. Conclusions To the best of our knowledge, this is the first case of FL that exhibited widespread erosions interspersed with proliferative lesions. Clinicians should be aware of oral FL or seek systemic factors in the presence of similar refractory oral erosions when treatment is non-responsive and the diagnosis is intractable.